2007
DOI: 10.1177/0739986307303237
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Modifying Effects of Education and Income on Hispanics Reporting Perceived Discrimination

Abstract: Research has shown that experiences of discrimination negatively affect health. However, little is known about whether socioeconomic position modifies the reporting of perceived discrimination. This cross-sectional study of 69 participants investigated the modifying effects of education and income on the reporting of perceived discrimination among Hispanics and Whites. Hispanics, compared to non-Hispanic Whites, of higher education (more than high school) and income ($30,000 or more per year) status are more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Level of education is known to increase expectations for career success and awareness of social inequalities (Forman et al 1997;Kessler et al 1999;Cardarelli et al 2007). Highly educated individuals may also be more likely to base their identity on their education and skills than less educated individuals.…”
Section: Educationmentioning
confidence: 99%
“…Level of education is known to increase expectations for career success and awareness of social inequalities (Forman et al 1997;Kessler et al 1999;Cardarelli et al 2007). Highly educated individuals may also be more likely to base their identity on their education and skills than less educated individuals.…”
Section: Educationmentioning
confidence: 99%
“…A second exploratory question was added to investigate the extent to which communication with care-givers is linked to active coping. In addition, we controlled for gender and aspects of SES given that prior research has found these characteristics are associated with several of the variables in this study (Brittian et al 2013; Cardarelli et al 2007). …”
Section: Study Purpose and Hypothesesmentioning
confidence: 99%
“…2003). This association has been shown to be moderated by education, acculturation, coping, social support and religious involvement (Bierman 2006, Cardarelli et al 2007, Noh et al 1999, Noh and Kaspar 2003, Prelow et al 2006).…”
Section: Introductionmentioning
confidence: 97%